PENGEMBANGAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE FONIK PADA TAMAN KANAK-KANAK BHAYANGKARI - Haryati Haryati (Universitas Khairun, 2015)
On of the important competences and must be masteredby childrenÂ are reading and writing. Because reading and writing competence supporting in some aspects of children language. From those competence starting introduce in pre school so they can progress in the future. Attention in phonic cah help children to progress strategies in understanding some words that rarely meet in daily activity. Context used for help children understand the meaning and the sounds and its sentences.